Ambient intelligence : 13th European Conference, AmI 2017, Malaga, Spain, April 26-28, 2017, Proceedings /: 13th European Conference, AmI 2017, Malaga, Spain, April 26-28, 2017, Proceedings. (2017) - Unknown
No abstract available